On-Chip Power Delivery and Management - Vaisband, Inna P.; Jakushokas, Renatas; Popovich, Mikhail; Mezhiba, Andrey V.; Köse, Selçuk; Friedman, Eby G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes methods for distributing power in high speed, high complexity integrated circuits with power levels exceeding many tens of watts and power supplies below a volt. It provides a broad and cohesive treatment of power delivery and management systems and related design problems, including both circuit network models and design techniques for on-chip decoupling capacitors, providing insight and intuition into the behavior and design of on-chip power distribution systems. Organized into subareas to provide a more intuitive flow to the reader, this fourth edition adds more than a hundred pages of new content, including inductance models for interdigitated structures, design strategies for multi-layer power grids, advanced methods for efficient power grid design and analysis, and methodologies for simultaneously placing on-chip multiple power supplies and decoupling capacitors. The emphasis of this additional material is on managing the complexity of on-chip power distribution networks.
From the Contents: Introduction -- Inductive Properties of Electric Circuits -- Properties of On-Chip Inductive Current Loops -- Electromigration -- Scaling Trends of On-Chip Power Distribution Noise -- High Performance Power Distribution Systems -- On-Chip Power Distribution Networks -- Computer-Aided Design and Analysis -- Closed Form Expressions for Fast IR Drop Analysis.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation